Seasonal influenza: Waiting for the next pandemic - Angela Clem; Sagar Galwankar (Journal of Global Infectious Diseases, 2009)
With the ongoing cases of H1N1 influenza (aka Swine Flu) occurring around the globe, seasonal influenza has a tendency to be overlooked by the media and general population as a source of illness and death. Yet, these pandemic influenza viruses arise from these seasonal influenza viruses. This article will provide an overview of seasonal influenza, its prevention and treatment, and the global surveillance system in place, used to detect the next influenza pandemic.